2017
DOI: 10.1002/ejoc.201701025
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Cascade Saegusa–Heck Reaction: Synthesis of β,β‐Diarylacroleins from Arylpropanals and Aryl Iodides

Abstract: An efficient and convenient Pd‐catalyzed Saegusa–Heck cascade protocol was developed, and its potential use in the synthesis of symmetrical and unsymmetrical β,β‐diarylacroleins in moderate to high yields was investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…This is, for instance, underlined by our observation that during the analogous Mizoroki–Heck couplings (Table ), no β,β-diarylation products were detected, although the aryl halides were used in excess and the reactions were conducted at elevated temperatures over long reaction times. A survey of pertinent literature confirms that Heck-type β,β-diarylation reactions of terminal alkenes or arylation reactions of α,β-disubstituted alkenes such as cinnamic acid derivatives indeed require much more forcing conditions (elevated temperatures, long reactions times, elaborate bases, and ligands) than the monoarylation of electron-deficient terminal alkenes. Analogous Matsuda–Heck couplings have scarcely been reported in the literature: Konno et al and Cacchi et al described successful Matsuda–Heck reactions of electron-deficient acyclic olefins with aliphatic substituents in the β-position and Taylor and Correia reported the stereoselective β-arylation of cinnamates . Very recently, Lucks and Brunner found that a heterogeneous catalyst system of Pd immobilized on AlPO 4 is particularly reactive in the β,β-diarylation of acrylates and a few other electron-deficient alkenes .…”
Section: Resultsmentioning
confidence: 98%
“…This is, for instance, underlined by our observation that during the analogous Mizoroki–Heck couplings (Table ), no β,β-diarylation products were detected, although the aryl halides were used in excess and the reactions were conducted at elevated temperatures over long reaction times. A survey of pertinent literature confirms that Heck-type β,β-diarylation reactions of terminal alkenes or arylation reactions of α,β-disubstituted alkenes such as cinnamic acid derivatives indeed require much more forcing conditions (elevated temperatures, long reactions times, elaborate bases, and ligands) than the monoarylation of electron-deficient terminal alkenes. Analogous Matsuda–Heck couplings have scarcely been reported in the literature: Konno et al and Cacchi et al described successful Matsuda–Heck reactions of electron-deficient acyclic olefins with aliphatic substituents in the β-position and Taylor and Correia reported the stereoselective β-arylation of cinnamates . Very recently, Lucks and Brunner found that a heterogeneous catalyst system of Pd immobilized on AlPO 4 is particularly reactive in the β,β-diarylation of acrylates and a few other electron-deficient alkenes .…”
Section: Resultsmentioning
confidence: 98%
“…Piko's team performed three-component domino reactions between -ketoesters, indoles and aryl boronates under experimental conditions [Eq. (36)] close to those used in the absence of the third component [see Eqs (34) and (35)]. [73] Studies of two-component coupling experiments led to favor a domino reaction involving firstly the coupling between the indole and the arylboronate [74] and subsequent reaction of the resulting OHR product with the dehydrogenated -ketoester, as depicted in Scheme 9.…”
Section: Domino Ohr + Ktr + Phrmentioning
confidence: 92%
“…The optimum conditions recently reported by the team of Xie and Shao [36] for the synthesis of ,-diarylacroleins from arylpropanals and aryl iodides, Ag2CO3 as the base [37] in AcOH under air [Eq. ( 7)], differ from those above.…”
Section: Domino Ktr + Hr(s)mentioning
confidence: 99%
“…Among the many methods, a palladium-catalyzed cross-coupling Mizoroki–Heck reaction has played a key role since it is widely used in different synthetic areas, i.e., pharmaceuticals, , fine chemicals, and organic semiconductors . Furthermore, slight modification of reaction conditions may also allow a consecutive series of Mizoroki–Heck reactions, obtaining synthetic advantages in terms of step-economy …”
Section: Introductionmentioning
confidence: 99%